Intervention Engagement Moderates the Dose–Response Relationships in a Dietary Intervention. Issue 1 (16th March 2016) - Lippke, Sonia; Corbet, Jana M.; Lange, Daniela; Parschau, Linda; Schwarzer, Ralf
Behavioral interventions could lead to changes in behavior through changes in a mediator. This dose–response relationship might only hold true for those participants who are actively engaged in interventions. This Internet study investigated the role of engagement in a planning intervention to promote fruit and vegetable consumption in addition to testing the intervention effect on planning and behavior. A sample of 701 adults (mean = 38.71 years, 81% women) were randomly assigned either to a planning intervention (experimental group) or to one of 2 control conditions (untreated waiting list control group or placebo active control group). Moderated mediation analyses were carried out. Significant changes over time and time × group effects revealed the effectiveness of the intervention. The effect of the intervention (time 1) on changes in behavior (time 3; 1 month after the personal deadline study participants set for themselves to start implementing their plans) was mediated by changes in planning (time 2; 1 week the personal deadline). Effects of planning on behavior were documented only at a moderate level of intervention engagement. This indicates an inverse U-shaped dose–response effect. Thus, examining participants' intervention engagement allows for a more careful evaluation of why some interventions work and others do not.